Subclinical central inflammation is risk for RIS and CIS conversion to MS. (October 2015) - Rossi, S; Motta, C; Studer, V; Macchiarulo, G; Germani, G; Finardi, A; Furlan, R; Martino, G; Centonze, D
Background: Subtle diffuse intrathecal inflammation is undetectable by conventional neuroimaging, and could influence multiple sclerosis (MS) disease course. Objective: To explore the role of subclinical persisting intrathecal inflammation in radiologically isolated syndrome (RIS) or clinically isolated syndrome (CIS) conversion to MS, and in early MS disease reactivation. Methods: One-hundred ninety-three subjects with RIS, CIS, relapsing–remitting (RR), or primary progressive (PP) MS were included, along with 76 matched controls. Cerebrospinal fluid (CSF) levels of interleukin-8 (IL-8), a major proinflammatory cytokine, were measured as a biomarker of intrathecal inflammation. Patients were followed up for 2 years. Clinical and imaging measures of disease progression were recorded. Results: High central contents of IL-8 were associated to clinical progression in subjects with RIS, and to the risk of conversion to MS in subjects with CIS. Asymptomatic intrathecal inflammation placed subjects at risk for MS conversion, even regardless lesion load. CSF IL-8 levels were higher in RR MS with high disease activity. Higher number of relapses in the first two years since diagnosis and shorter first inter-attack intervals were observed in patients with high levels of IL-8. Conclusion: IL-8 might provide utility in determining the presence of active intrathecal inflammation, and could be important in diagnostically undefined cases.